The market for electronic cash cards - Oz Shy; Juha Tarkka (Bank of Finland, 1998)
We develop a theoretical framework aimed to model the pricing of electronic money (electronic cash cards) and the market domain in which it will be used.We first calculate the fee structures of electronic cash- and charge-card industries for the monopoly and competitive cases.We show that the different market structures do not affect the domain of electronic cash cards and the displacement of currency in daily transactions.We provide a welfare analysis to determine whether a market equilibrium generates an underutilization or overutilization of the electronic cash cards relative to currency.Finally, we evaluate the threshold investment costs, both general and POS-specific, which would prevent the emergence of this industry.
URN:NBN:fi:bof-20140807449
Keywords: 330; Electronic Money; Smart Cards; Displacement of currency